Autotelic personality as a predictor of engagement in sports - Mikicin Mirosław (Sciendo, 2013)
Study aim: The aim of the study was to empirically evaluate the structure of autotelic personality of athletes in the context of engagement under competitive conditions. Material and methods: The study examined fifty athletes (volleyball players, basketball players, track and field athletes, rugby players and mountain bikers) following competitive events. The methodologies used included NEO-FFI Personality Inventory by Costa and McCrae to determine the level of personality traits and Flow Questionnaire (Csikszentmihalyi) to measure the level of subjective feeling of the state of engagement.